Links between the Aesthetic Education Environment of Schools and Pupils’ Artistic Self-Expression - Burkė, Aistė (Acta Paedagogica Vilnensia, 2019)
For a child, the school is like a separate “state” in which they are fully educated and influenced by a variety of environments, including aesthetic education. The significance of the environment in which the learner lives, matures, and creates has been found to be enormous. In Lithuania, there is a well-established “package” of environmental requirements for general education schools – educating, safe, functional, ergonomic, aesthetic. This article analyzes the relationship between the aesthetic education environment of the school and pupils’ artistic expression. Is it possible to develop the artistic self-expression of pupils in schools when creating an environment for aesthetic education? And is this a problematic question? The purpose of this article is to reveal the link between the aesthetic education environment of schools and pupils’ artistic expression. The following methods were used in the article: (1) an analysis of educational documents and scientific literature and (2) a review and comparative analysis of the realized projects. The educational document analysis method was used to review and analyze Lithuanian educational documents on school education environments. The analysis of educational documents on the educational environment of schools has led to the conclusion that a great deal of attention is paid to the ergonomic, functional, and aesthetic planning of educational spaces. The aim here is to create high standards for school education. The creativity of students, as well as the contribution of artistic self-expression, are identified as important aspects in creating an aesthetic education environment. The link between the creation and development of such an environment, and the involvement of the educational process participants in the creation of such spaces are emphasized. The creation of an aesthetic education environment in schools is more associated with visual and applied art. In applying the method of scientific literature analysis, this study includes a review of research conducted by Lithuanian and foreign authors about various school education environments, the influence of school education(s) on pupils’ learning, the aesthetic relationship of pupils with school education and the aesthetic education of schools; links between environmental and artistic activity are established. This article discusses the peculiarities and possibilities of modernizing the educational spaces of Lithuanian schools. After the analysis of scientific literature on the educational environment, it was concluded that the topics of the school educational environments were relevant to Lithuanian and foreign scientists. The environmental impact of school education was proven on the basis of a multi-faceted study; the concept of an aesthetic education environment has been revealed, its significance for personality development emphasized. The conclusion is that the aesthetic educational environment of a school can influence the formation of the students’ aesthetic attitudes. The active artistic expression of pupils can be provided by educators with certain conditions for their activities, or pupils can develop joint initiatives contributing to the creation of an aesthetic education environment. After discussing the modernization of the educational spaces of Lithuanian schools, an important link was identified between the creation of educational spaces and pupils’ artistic expression. The analysis of educational documents and scientific literature scientifically substantiated the link between the aesthetic environment of a school and pupils’ artistic expression. Examples of certain “dream school” projects in Lithuania and abroad were analyzed using the sample review method. This article contains an overview of the Lithuanian Primary School of the Veršvų Gymnasium in Kaunas (2018) and the Balsių Progymnasium in Vilnius (2011). Chosen for the review of foreign schools were the “Wish School” in Sao Paulo, Brazil (2016), We Grow and Blue School Preschool and Elementary Schools in New York, USA (2018), Lake Wilderness Primary School, Washington, USA (2017), Heart in Ikast International School and Multifunctional Center in Ikaste, Denmark (2018), Vittra Brotorp, Vittra Telefonplan, Vittra Södermalm School in Brotorp, Stockholm, Sodermalm, Sweden (2011–2012). An overview of architectural examples (analogues) implemented by Lithuania has revealed that Lithuanian architects can perfectly design schools that are modern, technologically equipped, ergonomic, etc. In the reviewed examples (analogies), the learning environment is safe and modern; they promote communality, creativity. The corridor system and the “four-walled” classrooms were retained in the design of Lithuanian schools. Pupils are encouraged to create and to participate in the creation of an aesthetic education environment through visual and applied art. Artistic self-expression is promoted by dancing, musical activities, and the like. Communality and a variety of after-school activities are promoted. An overview of architectural examples (analogues) implemented by foreign countries has revealed the latest architectural trends in global school design practice. It is noted that the design of new school buildings has been important for cities, societies, and education for decades. In many cases, the design process of the schools discussed was developed in conjunction with the needs of the community and adapted to the local architectural context. In the examples of foreign countries discussed, the functional zoning of premises was combined with modern design, educational principles, and the latest technologies. School interiors have been designed with a new concept of education and learning in mind. When designing the school spaces, it was emphasized that students are active subjects and space changers. In some of the examples of the discussed schools, the idea of a “class without borders” has been implemented. Non-formal seating, colorful furniture, and bright-colored walls are accentuated. Classrooms are modern and flexible and easily adaptable in accordance with the educational needs of the pupils. A diversity of activities, communication, and an atmosphere of creativity are promoted. Common spaces are easily adaptable and inspiring. Pupils’ artistic self-expression, curiosity, and the aim to “awaken” creativity are encouraged. Functional zoning allows students to work successfully together and independently. Attention is paid to communality and a diverse spectrum of activities. An overview of implemented Lithuanian and foreign architectural examples (analogues) has revealed the connection between the aesthetic environment of a school and the artistic expression of the pupils: 1) Students are encouraged to create and participate in the creation of an aesthetic education environment through visual and applied art; 2) Music, dance, and self-expression are promoted in school spaces; 3) The community is involved in the school design process. By comparing Lithuanian and foreign (analogous) examples, it may be stated that Lithuanian schools are well-planned and meet high standards. The interior spaces could be more colorful and playful. In the cases of foreign (analogous) countries, internal spaces are more characterized by informal seating places, vibrant and colorful furniture and walls. The corridor system is more boldly eschewed, and the concept of “classes without walls” is implemented.